Parenting Patterns in Students Character Building at Pondok Modern Darussalam Gontor Putri Campus 1 Mantingan Ngawi - Jihan El-Yunusi, Melikai; Abidin, Munirul; Bashith, Abdul (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
A parenting approach is used by Islamic boarding schools to raise generations with Islamic values. 24-hour complete life education is inextricably linked to the parenting approach used to mold the character of female students. This study aims to describe parenting patterns in shaping the character of female students, which includes parenting patterns in shaping the character of female students and methods for character development for female students at PMD Gontor Putri Campus 1. This study employs descriptive qualitative research methods. Interviews, observation, and documentation are all forms of data collecting, while strategies for data analysis include data reduction, data presentation, and conclusion-drawing. First, the study's findings indicate that there are four factors that influence parenting success and how it affects how female students behave. Second, in order for parenting styles to be successfully applied in developing students' character, a method must be used. The third strategy is to integrate three educational institutions (family, school, and community education) into one program to accomplish educational objectives in the development of female students' character. This strategy aims to create an integrative, comprehensive, and independent education system.